PENGARUH CITRA DESTINASI TERHADAP MINAT BERKUNJUNG KEMBALI KE OBYEK WISATA WADUK KEDUNG OMBO - Ihza Aditya Wisnu; Muhammad Sholahuddin (VALUE, 2023)
This study researches the effect of destination image on the interest in revisiting the Kedung Ombo Reservoir tourist attraction using a quantitative approach. Data collection in this study was carried out using a questionnaire questionnaire distributed online to visitors to the tourist attraction. The sample size of this study was 100 respondents, and data processing was conducted using IBM SPSS Statistics software version 21. The t-test analysis showed that partly cognitive and partly conative factors had a positive and significant effect on revisit interest, while Affective had a significant but weak effect. The implication of this study is that destination managers should prioritise improving cognitive and conative factors to increase visitors' interest in returning to Kedung Ombo Reservoir. The novelty of this study lies in its empirical findings, which contribute to the destination management literature regarding the influence of destination image on return visit interest.